Analisis Pengaruh Jumlah Penduduk, Pendidikan, Upah Minimum, Dan PDRB Terhadap Tingkat Pengangguran Terbuka Di Provinsi Jawa Barat - Fajar Rini Suhadi; Eni Setyowati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to analyze the effect of Population, Education, Minimum Wage, and GRDP on the Open Unemployment Rate in West Java Province with 26 Regencies/Cities in West Java Province in 2018-2020. This study uses the panel data method using software eviews 10. From the results of the study it can be concluded that partially Education, Minimum Wage and Gross Regional Domestic Product have a negative and significant effect on the Open Unemployment Rate, while the Population Number variable has no effect on the Open Unemployment Rate variable. The simultaneous influence of the variables of Education, Minimum Wage and Gross Regional Domestic Product is significant at 92.51% and the remaining 7.49% is influenced by other factors that are not included in the model. Unemployment rate is open in every Regency/City in West Java Province.